A Comparative Legal Study: Euthanasia for Psychological Reasons - Taufik Muhlisani Ihsan, Muhammad Ficqhi; Kamal, Muhammad; Aswari, Aan (Manunggal Halim Jaya, 2024)
This research conducts a comprehensive examination of euthanasia within the legal frameworks of Indonesia and the Netherlands, aiming to elucidate the criminal liability associated with this act. Employing a normative legal research approach, the study analyzes written legal materials, including regulations, legislation, books, journals, and related legal sources, to facilitate a cross-jurisdictional comparison. The findings reveal distinctive legal perspectives in the two countries. In the Netherlands, euthanasia was initially deemed a criminal offense under penal code sections 293 and 294. However, the landscape evolved with the enactment of the Dutch Law on Termination of Life on Request and Assisted Suicide in 2001. This legislation, effective from April 1, 2002, decriminalized euthanasia under specific conditions. Conversely, in Indonesia, euthanasia, particularly active euthanasia, lacks explicit recognition in positive law. Despite the absence of clear regulations, it is generally treated as a form of murder due to its implication in ending a person's life. Examining criminal liability in Indonesia, the study identifies article 344 of the Criminal Code as the closest provision related to euthanasia. However, detailed regulations are lacking. Additionally, the medical code of ethics plays a role in shaping responsibility. Doctors violating article 7d of the medical code of ethics, which mandates the immediate protection of human life, particularly patients, may face consequences. In conclusion, this research underscores the contrasting legal stances on euthanasia in Indonesia and the Netherlands. While the Netherlands has embraced a legalized and regulated framework, Indonesia's legal landscape remains silent on the matter. The study also highlights the need for clearer legal provisions in Indonesia and emphasizes the role of medical ethics in shaping the responsibility associated with euthanasia.